Efficiency of Matricaria chamomilla CH12 and number of doses of rabies vaccine on the humoral immune response in cattle - Reis, Luis Souza Lima De Souza (2008)
This study evaluated the effect of Matricaria chamomilla and vaccination frequency on cattle immunization against rabies. Four groups (n = 15 /group) were treated with or without Matricaria chamomilla CH12 and vaccinated with one or two doses of rabies vaccine (30 day interval). No effect of chamomile was found on cattle immunization against rabies; however, antibody titers were protective in cattle vaccinated twice, while 93.3% of cattle vaccinated only once had titers under 0.5 UI/ml after 60 days. In conclusion, the use of chamomile did not alter the humoral immune response in cattle, and two vaccine doses are suggested for achieving protective antibody titers.